Spinning - Sarmiento, Irene Carolina A. (Anvil, 2009)
"This story goes out to children with autism, their families, their teachers, and all those who care for them. Signs of autism include: not speaking or making eye contact, lack of social interaction, and being emotionally unresponsive. Children with autism may also do 'odd' repetitive things like flap their hands or twist their fingers. They may have rituals like arranging toys and household objects in a certain way. As in the title, 'spinning' (or 'twirling') is one such repetitive behavior seen in some children with autism. the story aims to highlight what children with autism are capable of being and sharing with others as whole human beings. It seeks to look beyond their handicaps and differences, and see how special these children truly are, with their own special gifts and abilities"--Author's note.